2001
DOI: 10.1038/sj.cdd.4400944
|View full text |Cite
|
Sign up to set email alerts
|

Endonuclease G: a mitochondrial protein released in apoptosis and involved in caspase-independent DNA degradation

Abstract: A hallmark of apoptosis is the fragmentation of nuclear DNA. Although this activity involves the caspase-3-dependent DNAse CAD (caspase-activated DNAse), evidence exists that DNA fragmentation can occur independently of caspase activity. Here we report on the ability of truncated Bid (tBid) to induce the release of a DNAse activity from mitochondria. This DNAse activity was identified by mass spectrometry as endonuclease G, an abundant 30 kDa protein released from mitochondria under apoptotic conditions. No tB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
202
3
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(213 citation statements)
references
References 23 publications
5
202
3
3
Order By: Relevance
“…As previously described, some of the events thought to significantly contribute to the pathophysiological changes following acute SCI include disruption of the mitochondrial inner membrane potential and formation of the mPTP, leading to mPT and cell death via necrosis [83][84][85][86], as well as programmed cell death mechanisms [87][88][89][90][91][92][93]. Therefore, promoting mitochondrial function by limiting mPTP formation and subsequent mPT may have significant therapeutic benefits for the treatment of acute SCI.…”
Section: Targeting the Mptp In Acute Scimentioning
confidence: 99%
“…As previously described, some of the events thought to significantly contribute to the pathophysiological changes following acute SCI include disruption of the mitochondrial inner membrane potential and formation of the mPTP, leading to mPT and cell death via necrosis [83][84][85][86], as well as programmed cell death mechanisms [87][88][89][90][91][92][93]. Therefore, promoting mitochondrial function by limiting mPTP formation and subsequent mPT may have significant therapeutic benefits for the treatment of acute SCI.…”
Section: Targeting the Mptp In Acute Scimentioning
confidence: 99%
“…21,22 We found that AIF continued to remain in the mitochondrial compartment upon neurodegenerative stimuli in ETNA cells 72 h after G93A-SOD1 transfection or 96 h after Ab application (Figure 6a, b), both in the presence and absence of apoptosome. Similarly, when cytochrome c was released in ETNA cells, the Endonuclease G (EndoG), a factor also known to trigger a caspase-independent type of death, 23 was retained in the mitochondria and did not contribute to any delayed forms of cell death ( Figure 6c). Release of both AIF and EndoG from ETNA À/À cells mitochondria remain intact after cytochrome c release induced by neurodegenerative stimuli…”
Section: Etna Cells Apoptosis Induced By Neurodegenerative Stimuli Ismentioning
confidence: 99%
“…EndoG is localized in the mitochondria, and then translocates to the nucleus during apoptosis with cell death stimuli such as truncated Bid (tBid), tumor-necrosis factor-alpha (TNF-a) and UV irradiation. 6,7 Thus, EndoG joins other mitochondrial proteins including cytochrome c, Omi/ HtrA2, Smac/DIABLO and apoptosis-inducing factor (AIF) as cell death effectors that are sequestered in the mitochondria, but released during the cell death process. However, the exact role and relevance of EndoG in apoptosis is controversial.…”
Section: Introductionmentioning
confidence: 99%